Review of Accounting Sustainability Using Analytical Procedure: Applied Study on GCC Industrial Companies - Abu Zerr, Afaf; Atoum, Radi (Jordan Journal of Business Administration, 2015)
The study aims at analyzing and developing sustainability indicators to serve accounting and financial sustainability philosophy, to attain that, GCC large companies' financial data, and board of directors reports were analyzed. To achieve the paper goal, researchers analyzed CAMELs indicators, whereas, they developed a group of indicators concerning openness and sensitivity. In addition they have added five indicators to the CAMELs group of KPIs. Thereby, researchers have developed the concept of CAMELs approach of analysis to be the CAPPELO approach. What is actually developed are adding group of KPIs that analyzes Productivity; which is non-financial KPIs that have a major impact on sustainability due to its direct effect on companies' competencies. The study conclude that, almost all GCC companies have a strategic and financial plans, but few of them have beard high risks in order to have an alternative finances. However, many companies have relied on self revenue to finance their activities. Therefore, the disparity in companies' abilities in investing their resources have led the deviations in their ability to be financially sustainable. This fact is beyond the major differences in their aptness to social and environmental responsibility. GCC companies characterized by it domestic property; 99% of their shares are owned by citizens. The group of indicators analyzed were shown differences between GCC countries, many have high rates in certain KPIs others have less depending on companies management of human and financial resources. The study recommends that GCC companies like others have to pay more focus on accounting and financial awareness, especially, legislative entities, accounting professional entities, and financial stock commissions to support Corporate Social Responsibility CSR legislations and, have their commitment to issue a periodical sustainability reports. Moreover, they have to build an early warning system that help in predicting financial and technical crises, and set the means to mitigate, alleviate and/or minimize crises impacts.